2016
DOI: 10.1177/1687814016649326
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study of flow field on molten iron desulfurization with mechanical stirring

Abstract: The flow field of molten iron in the desulfurization process utilizing the mechanical stirring method under three different conditions was investigated using numerical simulation. The three conditions were central and eccentric stirring with the standard impeller and central stirring with the worn impeller, respectively. Three 1/20-scale numerical models were established and four inspection regions were set up on them. In all, 600 sets of instantaneous velocity fields for each model were exported and proper or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Plenty of literature has been published on the experimental aspects of the KR process, e.g. impeller practice [3][4][5][6], particles addition mode [7,8], operation parameters improvement [9][10][11], stirring mode changing [6,[12][13][14][15], adding barriers (such as baffle or pin fins) in the molten pool [6,16,17]. The problem of desulphurizer low utilization rate has been improved to some extent, but some of the results are difficult to operate in desulphurization practice, which limits the improving of reagent efficiency fundamentally.…”
Section: Introductionmentioning
confidence: 99%
“…Plenty of literature has been published on the experimental aspects of the KR process, e.g. impeller practice [3][4][5][6], particles addition mode [7,8], operation parameters improvement [9][10][11], stirring mode changing [6,[12][13][14][15], adding barriers (such as baffle or pin fins) in the molten pool [6,16,17]. The problem of desulphurizer low utilization rate has been improved to some extent, but some of the results are difficult to operate in desulphurization practice, which limits the improving of reagent efficiency fundamentally.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to its reduced order and feature extraction characteristics, POD methods are increasingly being used to study complex flow phenomena. For example, Xiao et al [16] obtained numerical simulations of molten iron flow fields in three different desulfurization processes and used POD to analyze flow field data. e analysis concluded that eccentric agitation is most conducive to desulfurization.…”
Section: Introductionmentioning
confidence: 99%